ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT DALAM PEMANFAATAN OBAT TRADISIONAL DI DESA PANCASARI - Gandisha Sandili; Ni Putu Aryati Suryaningsih; Dewa Ayu Putu Satrya Dewi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Traditional medicine is now no longer a taboo subject for the community, currently many people's lifestyles lead back to nature by using herbal medicines, one of which is increasing the use of these herbal medicines so that it is necessary to analyze the factors that influence the behavior of the Pancasari Village community in the use of traditional medicine.To determine the influence of factors that underlie people's behavior regarding the use of traditional medicines in Pancasari Village.This research is a type of observational research that is descriptive quantitative, with the research design used is Cross Sectional and the sampling technique used in this research is the Side Purposive Technique. The number of samples is 96 respondents, data management uses SPSS by analyzing Univariate Test data and Logistic Regression Analysis.Logistic Regression Analysis of sociodemographic factors on people's behavior in using traditional medicines in Pancasari Village, there are several factors that influence people's behavior in using traditional medicines in Pancasari Village with a significant value, namely the age factor p-value = 0.045 (p <0.05 ), income factor p-value = 0.034 (p<0.05), and occupational factors that obtain a significant p-value = 0.042 (p<0.05). Plants that are often used by the community in the use of traditional medicine are ginger/red ginger to treat throat problems by 15 people (15.6%), turmeric for treating menstrual pain by 10 people (10.4%), and lime for increased endurance and overcome acne problems as many as 10 people (10.4%).There is an influence of age, income and occupation on people's behavior in the use of traditional medicines in Pancasari Village, Buleleng Regency.